Specification of a Model of Migratory Identity - López de Nava Tapia, Sofía (Trabajo Social UNAM, 2016)
Migration is a phenomenon made up of three spaces: centrality, trans-periphery and periphery as socio-economic, socio-political and psycho-social determinants. The aim of the present paper is to propose a model for opening a discussion on the establishment of migration as a central theme on the trilateral agenda. In this sense, various theories and concepts are reviewed in order to specify in a model the relations between migratory identity and indicators such as: depression, aggression, insults, injustice, anxiety, danger, despair, panic, revenge and discrimination. Finally, it is pointed out that the importance of this study is to take into account at least four logics: adaptation, assimilation, contingency and identity for the analysis of news and predictions of scenes of conflict between those who govern and those who are governed.